Spatial pattern distribution of dengue fever in sub-urban area using GIS tools - Masnita Md Yusof,; Nazri Che Dom,; Ariza Zainuddin, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Dengue fever (DF) is one of the major public health problems in Malaysia. The number of cases recorded is always fluctuating. The aim of the study is to identify the high-risk area for the occurrence of dengue disease. Spatial-temporal model was used by measuring three characteristics which are frequency, duration and intensity to define the severity and magnitude of outbreak transmission. This study examined a total of 386 registered dengue fever cases, geo-coded by address in Jempol district between January 2011 and December 2015. Even though case notification figures are subjected to bias, this information is available in the health services. It may lead to crucial conclusion, recommendations, and hypotheses. Public health officials can utilize the temporal risk indices to describe dengue relatively than relying on the traditional case incident figures.